DETERMINANTS OF RETURN ON INVESTMENT IN RETAIL COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (2020–2024) - Theresia Mega Tiara; Zuraidah; Rusnaidi (Journal Informatic, Education and Management (JIEM), 2026)
The purpose of this study is to analyze the influence of current ratio (CR), return on equity (ROE), debt to asset ratio (DAR), inventory turnover (ITO), and sales growth (SG) on return on investment (ROI) in retail companies listed on the Indonesia Stock Exchange from 2020 to 2024. The study used secondary data from 19 retail companies with a total of 95 observations and analyzed them using multiple linear regression. The results of the study show that ROE and DAR have a partial effect on ROI, while CR, ITO, and SG do not. However, all variables simultaneously affect ROI. These findings suggest that profitability and financing structure play a significant role in enhancing the return on investment of retail companies.